CHARACTER DEPICTION WITH BEHAVIORAL PROCESS IN 'NOUVELLES VERTES' SHORT STORIES - Prasetyo, Gilang Tegar; Sajarwa (Leksema: Jurnal Bahasa dan Sastra, 2024)
This study aims to describe the forms of clauses with behavioral processes that explain characterizations in the short story anthology Nouvelles Vertes, and the characterization techniques realized by the behavioral processes. This research uses a descriptive approach with qualitative method. The data of this research are clauses that explain characterization with behavioral process in the short stories of Nouvelles Vertes anthology. This research uses the theory of Systemic Functional Linguistics by Halliday and Matthiesen (2014) and characterization technique by Nurgiyantoro (2018). The results show that there are three types of behavioral processes used to explain characterization, i.e. verbal, mental, and physical. The characterization techniques realized with behavioral processes are in the form of character reaction techniques and thoughts and feelings techniques. The tendency to use behavioral processes with character reaction techniques shows that each event in the short story directly affects the character's behavior in terms of speech, actions, and feelings.